Mutual support groups for women victims of domestic violence - Tenorio Castro, Milena (2009)
In this article, concepts related to domestic violence against women will be developed in order to understand the cognitive and emotional world of the victim, how she confronts her reality and why is so difficult to break up with this cycle of domestic violence in which she is immersed. However, the central theme in this article is my own professional experience with mutual support groups, as a therapeutic technique for women victims of psychological abuse, its objective anddynamics.